Formulasi dan Stabilitas Mikroemulsi O/W sebagai Pembawa Fucoxanthin - Lutfi Suhendra; Sri Rahardjo; Pudji Hastuti; Chusnul Hidayat (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The objective of this study was to obtain a clear and stable oil-in-water (o/w) microemulsion containing fucoxanthinwhich is intended for aqueous food system application. Virgin coconut oil (VCO) was used as the oil phase andcombination of Tween 80, Tween 20 and Span 80 were selected as nonionic surfactant having high, medium, and lowHLB (Hydrophilic-Lipophilic Balance) values, respectively. The o/w microemulsions were formulated to have the Þ nalHLB values of 13.5, 14.0, and 14.5. For each HLB value, three different microemulsion formulas were determined. Allof the formulated microemulsions were then subjected to oven heating at 105 oC for 5 hour, centrifugation at 4500 rpmfor 30 min, incubation at different pH (3.5, 4.5, and 6.5), water dilution, and photooxidation to evaluate its stability.The most stable microemulsion was then selected and used to deliver fucoxanthin as a hydrophobic antioxidant inaqueous system. Photo-oxidation was performed by exposing the microemulsions under ß uorescent light at 4,000 luxfor up to 4 hours at room temperature. Peroxide values were measured every hour using ferric thiocyanate method.Stable o/w microemulsions were obtained when its HLB value was 14.5, the ratio of oil:surfactants was 3:17, andthe ratio of (oil + surfactants) : water was 35 : 65. The ratio of Tween 80 : Tween 20 : Span 80 was 92.0 : 2.5: 5.5. Fucoxanthin microemulsion was remained stable at pH range from 3.5 to 6.5 even after heating treatment,centrifugation, and water dilution. However, there were increased peroxide values of these microemulsions after being subjected to photooxidation. The presence of fucoxanthin (over 12 ppm) in the microemulsion could not effectively inhibit photooxidation of the o/w microemulsion.ABSTRAKTujuan penelitian ini adalah untuk memperoleh mikroemulsi minyak dalam air (o/w) yang mengandung fucoxanthinyang stabil dan jernih untuk diaplikasikan dalam sistem makanan aqueous. Virgin coconut oil (VCO) digunakansebagai fase minyak dan kombinasi Tween 80, Tween 20 dan Span 80 sebagai surfaktan non ionik yang masingmasingmempunyai nilai HLB (Hydrophilic-Lipophilic Balance) tinggi, medium dan rendah. Formulasi mikroemulsio/w ditentukan nilai HLB akhir masing-masing 13,5; 14, dan 14,5. Masing-masing nilai HLB tersebut ditentukan tigaformula yang berbeda. Semua formulasi mikroemulsi kemudian dipanaskan dalam oven pada suhu 105 oC selama 5jam, disentrifugasi pada kecepatan 4500 rpm selama 30 menit, diinkubasi pada pH yang berbeda (3,5; 4,5 dan 6,5),diencerkan dengan akuades dan stabilitas diuji secara fotooksidasi. Mikroemulsi paling stabil selanjutnya dipilih dandigunakan untuk pembawa fucoxanthin sebagai antioksidan hidrofobik dalam sistem aqueous. Fotooksidasi ditentukandengan menempatkan mikroemulasi di bawah sinar ß ouresensi 4000 lux selama 4 jam pada suhu ruang. Angkaperoksida diukur setiap jam menggunakan metode feri thiosianat. Mikroemulsi o/w yang stabil diperoleh pada HLB14,5 dengan rasio minyak : surfaktan = 3 : 17 dan rasio minyak + surfaktan : air = 35 : 65. Rasio Tween 80 : Tween 20: Span 80 adalah 92.0 : 2.5 : 5.5. Mikroemulsi fucoxanthin yang diperoleh stabil pada pH 3,5 sampai 6,5 dan bahkansetelah perlakuan pemanasan, sentrifugasi dan pengenceran. Namun angka peroksida meningkat selama fotooksidasi.Fucoxanthin dalam mikroemulasi lebih dari 12 ppm tidak efektif untuk menghambat fotooksidasi dalam mikroemulsio/w.